2005
DOI: 10.1179/136485905x51508
|View full text |Cite
|
Sign up to set email alerts
|

High-level cerebellar expression of cytokines and adhesion molecules in fatal, paediatric, cerebral malaria

Abstract: Although the roles played by systemic tumour necrosis factor (TNF) and interleukin 1beta (IL-1beta), and their upregulation of intercellular adhesion molecule 1 (ICAM-1), vascular cell adhesion molecule 1 (VCAM-1) and E-selectin, in the pathogenesis of human cerebral malaria (CM) are well established, the role of local cytokine release, in the brain, remains unclear. Immunohistochemistry was therefore used to compare the expression of ICAM-1, VCAM-1, E-selectin, IL-1beta, TNF and transforming growth factor bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 47 publications
2
73
0
3
Order By: Relevance
“…The discovery of a reliable laboratory test that accurately identifies individuals at risk of developing fatal CM would be a valuable tool. Human studies have revealed tight association between levels of specific chemokines and CM mortality [4,5,12,41,[43][44][45]67]. Thus, understanding the alterations in cytokine or chemokine homeostasis in CM patients will elucidate the underlying pathogenesis and identify potential predictive prognostic biomarkers for CM mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of a reliable laboratory test that accurately identifies individuals at risk of developing fatal CM would be a valuable tool. Human studies have revealed tight association between levels of specific chemokines and CM mortality [4,5,12,41,[43][44][45]67]. Thus, understanding the alterations in cytokine or chemokine homeostasis in CM patients will elucidate the underlying pathogenesis and identify potential predictive prognostic biomarkers for CM mortality.…”
Section: Discussionmentioning
confidence: 99%
“…TNF levels increase with disease severity and are maximal in severe malaria patients, both with P. falciparum and P. vivax (Hemmer et al 1991(Hemmer et al , 1994Deloron et al 1994;Perlmann et al 1997;Holst et al 1999;Luty et al 2000;Perkins, Weinberg andKremsner 2000, Lyke et al 2004;Duarte et al 2007;Guiyedi et al 2007;Tchinda et al 2007;Raza et al 2013). Highest brain levels of TNF are observed in P. falciparum patients who died from cerebral pathology (Maneerat et al 1999;Armah et al 2005). Despite the pathogenic role of TNF in malaria pathology, deficiency of TNF or TNFR1 has no effect on murine CM (Hermsen et al 1997;Lucas et al 1997a,b;Engwerda et al 2002;Piguet, Kan and Vesin 2002a;Hansen et al 2004;Parekh et al 2006;Togbe et al 2008).…”
Section: Cytokines and Other Soluble Inflammatory Mediatorsmentioning
confidence: 99%
“…Neuronal ANG1 and ANG2 staining are associated with microhemorrhages, whereas no association is found with parasite sequestration. ICAM-1 is also increased in the cerebral endothelium of CM patients (Ockenhouse et al 1992;Turner et al 1994;Armah et al 2005), and may augment parasite sequestration (Bengtsson et al 2013). Also in P. vivax infections markers of endothelial activation are increased and correlate with severity and with peripheral parasitemia (Ohnishi 1999;Raza et al 2013;Gomes et al 2014).…”
Section: Excessive Endothelial Activationmentioning
confidence: 99%
“…The pathogenesis of CM is still not well understood although it is clearly multifactorial, involving sequestration of P. falciparum infected erythrocytes to brain vasculature, triggering inflammatory cytokine responses and apoptotic pathway leading to a breach and dysfunction of the blood brain barrier, tissue damage and repair [26][27][28][29]. In an attempt to understand the pathogenesis of CM, our previous studies in Ghana [30] and India [31] for the first time revealed a striking association between the chemokine interferon inducible protein-10 (CXCL10-) and CM severity, suggesting that CXCL10 may be a biomarker for CM severity.…”
Section: Proposed Biomarkers For Cerebral Malariamentioning
confidence: 99%